A Comprehensive Study and Analysis of LEACH and HEED Routing Protocols for Wireless Sensor Networks – With Suggestion for Improvements - G. Anitha; V. Vijayakumari; S. Thangavelu (Institute of Advanced Engineering and Science, 2018)
The main interesting aspect of the digital era is the widely spread ease of communication from one end of the world to the other end of the world. There is a revolution in communication, digitalization, globalization, video calling, wireless data transfer and this is possible due to networking. Initially computer networks is the data sharing where data such as documents, file, reports, presentation files, videos, images etc can be shared within a local network or remotely connected networks. Traditional data networking is to empower end-to-end information transfer. The data in such networks are carried across point-to-point links and the intermediate nodes just forward the packets, where the payload of the packets is not modified. Traditional LANs need wires, which may be difficult to set up in some situations.It is very much understandable and clearly visible that wired communication is being completely overtaken by wireless technologies in the recent past. Wireless LANs, by its very nature, empowers with increased mobility and flexibility. Wi-Fi devices get connected to the internet through WLAN and access points. 2.4 GHz and 5 GHz ISM bands are used by Wi-Fi. Also, it is to be understood that, a wireless adhoc network is distributed in its nature. It is also to be noted that, the adhoc nature makes these network to rely on any of the pre-existing infrastructure. The data forwarding shall happen from the nodes very much dynamically based on the connectivity and the routing algorithm used.